EXTERNALIZATION OF THE MULTICULTURAL ISLAMIC EDUCATION CURRICULUM AT SCHOOL - Muhammad Sulistiono; Maskuri Maskuri; Nur Fajar Arief (Journal Education Multicultural of Islamic Society, 2022)
This research discusses the externalization of multicultural Islamic education which has the same wedge in the realm of learning, namely a contextual approach. So that externalization is a process of material association with application in everyday life, namely returning to the values that guide the life of the community. The search for multicultural values that became the foundation for the founding of the school. Then it turned into a guideline by the citizens of the school that reflected the experience of multicultural values. Furthermore, it is used as a foundation in the multicultural Islamic religious education curriculum. Based on the researcher's findings on the focus of research on the externalization of the multicultural Islamic education curriculum in schools which includes several aspects, namely; (1) the phenomenon of ideas, (2) the phenomenon of history, (3) the phenomenon of the reaction of society, (4) the phenomenon of social products.Keywords: externalization, curriculum, multicultural Islamic education